Enjoyment and affective responses to two regimes of high intensity interval training in inactive women with obesity. Issue 10 (26th November 2019) - Astorino, Todd A.; Clark, Amy; De La Rosa, Annie; De Revere, Jamie L.
ABSTRACT: This study examined changes in enjoyment, affective valence, and rating of perceived exertion (RPE) in obese women performing two regimes of high intensity interval training (HIIT) differing in structure and volume. Nineteen obese and inactive women (age and body mass index = 37.5 ± 10.5 yr and 39.0 ± 4.3 kg/m 2 ) were randomized to 6 wk of traditional (TRAD, n  = 10) or periodized interval training (PER, n  = 9) which was performed on a cycle ergometer during which structure changed weekly. Two supervised sessions per week were performed in a lab, and one session per week was performed unsupervised. During every lab-based session, perceptual responses including enjoyment, affective valence, and RPE were acquired. Data showed a groupXtraining interaction for enjoyment ( p  = 0.02) which was lower by 10–25 units during PER versus TRAD. In addition, there was a groupXtimeXtraining interaction for RPE ( p  = 0.01). RPE did not change in response to TRAD yet varied during PER, with lower RPE values exhibited during brief supramaximal bouts (6.3 ± 0.9) compared to longer intervals (7.3 ± 1.2). Both regimes showed reductions in affective valence during training, with the lowest values equal to 1.5 ± 1.6 in TRAD and −0.2 ± 1.6 in PER. Compared to TRAD, more aversive responses were shown in PER throughout training by 0.4–2.0 units. Data show lower enjoyment and more aversive responses to higher-volume bouts of interval training, which suggests that shorter bouts may be perceived more favourably by obese women.